Sustaining Prosperity: Exploring Fiscal and Financial Sustainability in the Context of Dynamic Fiscal Policy - Limoa, William S; Weku, Christoffel E F (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores how fiscal policy and financial sustainability support sustainable economic prosperity amid global instability. It examines the impact of government taxation and spending decisions on economic outcomes, aggregate demand, employment, inflation, social welfare, infrastructure development, and income inequality. Financial sustainability is analyzed through prudent fiscal management and debt sustainability, focusing on long-term government finance viability and mitigating fiscal risks. Research Design and Methodology: The study employs a qualitative methodology, incorporating a comprehensive literature review of theoretical works, empirical studies, and policy analyses. Data is collected through systematic reviews of scholarly articles, books, policy reports, and official publications. Thematic analysis techniques, including coding and categorization, synthesize findings, with reflexivity to consider assumptions and biases. Findings and Discussion: The research underscores the importance of flexibility and adaptability in fiscal policy, highlighting automatic stabilizers and countercyclical policies for economic stabilization and sustainable growth. Prudent debt management, including debt restructuring and fiscal consolidation, is vital for mitigating fiscal risks and ensuring debt sustainability. The findings emphasize integrating fiscal sustainability with broader economic and social goals and the need for institutional reforms and international cooperation to enhance fiscal governance. Implications: The study provides insights for policymakers on the importance of fiscal prudence and sustainability. It advocates for a balanced approach that addresses short-term stabilization and long-term goals and calls for institutional reforms to improve fiscal discipline, transparency, and accountability. By integrating interdisciplinary perspectives, policymakers can develop resilient and sustainable fiscal policies that promote long-term prosperity and social equity.